Development and Validation of a Stability-indicating Method for Neostigmine Bromide: Separation, Identification and Characterization of Degradation Product using LC-MS and ESI-Q-TOF-MS/MS - Makkar, Rajan; Singh, Jitender; Bhardwaj, Monika; Mehta, Lovekesh; Grover, Parul (Indian Journal of Pharmaceutical Education and Research, 2022)
Objectives: Forced degradation study of the drug product and drug substance is very much important in drug development and drug discovery to establish the intrinsic stability and understand its behaviors towards different stress conditions. In the present work, stress testing of neostigmine bromide (NBr) was carried out as per ICH guidelines to identify and characterize the degradation product (DP) formed. Materials and Methods: According to ICH guidelines, drug substance was subjected to various degradation conditions. Waters BEH (Ethylene Bridge Hybrid) C-18 column (1.7 m, 100 mm 2.1 mm) having the composition of mobile phase Eluent A: 0.01M KH2PO4 in water pH-2.5 with orthophosphoric acid and Eluent B: Acetonitrile utilizing 220 nm wavelengths provided the best separation of DP and drug component. Throughout the analysis, the injection volume (5 μL) and flow rate (0.3 mLmin -1) were kept constant. Results: The limits of detection (LOD) and quantitation (LOQ) were set at 25 ngmL-1 and 50 ngmL-1, respectively. The method showed excellent linearity over a concentration range of 25-250 ngmL-1 with a regression coefficient (R2) value of 0.9999. The results showed that significant degradation was observed in base and oxidative degradation conditions whereas found in neutral, acidic, photolytic and thermal degradation conditions. Conclusion: The DP was identified and characterized using a sophisticated HRMS/MS/TOF approach for accurate mass measurement using the ESI positive mode of ionization. In the present study, the establishment of the degradation pathway of drug substance and fragmentation pathway of DP-I were explained which was never reported in any literature.
Keywords: Neostigmine bromide; RP-UPLC; Stability-indicating; Stress study; Validation